1996
DOI: 10.3171/jns.1996.85.2.0310
|View full text |Cite
|
Sign up to set email alerts
|

Orientation landmarks of endoscopic transaxillary T-2 sympathectomy for palmar hyperhidrosis

Abstract: The identification of the T-2 ganglion through a narrow operative viewfield is the greatest challenge in performing endoscopic transaxillary T-2 sympathectomy, especially for a surgeon who is unfamiliar with the technique. The authors describe a simple anatomical method for identifying the T-2 ganglion during the operation, based on a study of 17 adult cadavers. First, a similar clinical procedure was performed along the anterior or middle axillary line via the second to fourth intercostal spaces to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…In most cases, they found that the upper margin of the T2 ganglion was at the second intercostal space near the upper border of the third rib [1]. In addition, the lower end of stellate ganglion is located at the second intercostal space near the lower margin of the second rib.…”
Section: Discussionmentioning
confidence: 97%
“…In most cases, they found that the upper margin of the T2 ganglion was at the second intercostal space near the upper border of the third rib [1]. In addition, the lower end of stellate ganglion is located at the second intercostal space near the lower margin of the second rib.…”
Section: Discussionmentioning
confidence: 97%
“…The T2 sympathetic ganglion lies between the second and [9,10]. The superior intercostal artery plays a critical role in identifying the second rib [3,15]. This small vessel arising from the subclavian artery exists in 87.5% of the cadavers studied and consistently runs laterally and parallel to sympathetic chain at an average distance of 10 mm at the second rib [3].…”
Section: Discussionmentioning
confidence: 99%
“…The superior intercostal artery plays a critical role in identifying the second rib [3,15]. This small vessel arising from the subclavian artery exists in 87.5% of the cadavers studied and consistently runs laterally and parallel to sympathetic chain at an average distance of 10 mm at the second rib [3]. The second rib is just beneath the first intercostal muscle, offering another identification method.…”
Section: Discussionmentioning
confidence: 99%
“…Una vez identificada la cadena simpática como un cordón blanco que cruza perpendicularmente sobre el cuello de las costillas, es conveniente asegurarse del nivel mediante fluoroscopia (Figura 5) 10 . En pacientes con hiperhidrosis palmar, que es la indicación más frecuente, suele llevarse a cabo una lesión del ganglio simpático T2, que puede extenderse hasta los ganglios T3 y T4, aunque la mayoría de los autores coinciden en que no es necesario salvo hiperhidrosis axilar asociada, ya que podría incrementar la tasa y el grado de hiperhidrosis compensatoria y la sequedad de las manos 18,49,51 .…”
Section: Figura 1 Introducción De La Vaina Y El Endoscopio Por El 4ºunclassified